Relative Prognostic Significance of Positron Emission Tomography Myocardial Perfusion Imaging Markers in Cardiomyopathy. (20th October 2021) - Thomas, Merrill; Sperry, Brett W.; Peri-Okonny, Poghni; Malik, Ali O.; McGhie, A. Iain; Saeed, Ibrahim M.; Chan, Paul S.; Spertus, John A.; Thompson, Randall C.; Bateman, Timothy M.; Patel, Krishna K.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Rubidium-82 positron emission tomography myocardial perfusion imaging provides measurements of perfusion, myocardial blood flow and reserve (MBFR), and changes in left ventricular ejection fraction (LVEF) at rest and peak stress. Although all of these variables are known to provide prognostic information, they have not been well studied in patients with heart failure due to reduced LVEF. Methods: Between 2010 and 2016, 1255 consecutive unique patients with LVEF≤40% were included in this study who underwent rubidium-82 positron emission tomography myocardial perfusion imaging and did not have subsequent revascularization within 90 days. Perfusion assessment was scored semiquantitatively, and LVEF reserve (stress-rest LVEF) and global MBFR (stress/rest MBF) were quantified using automated software. Cox proportional hazards models adjusted for 14 clinical and 7 test characteristics were used to define the independent prognostic significance of MBFR on all-cause mortality. Results: Of 1255 patients followed for a mean of 3.2 years, 454 (36.2%) died. After adjusting for clinical variables, the magnitude of fixed and reversible perfusion defects was prognostic of death ( P =0.02 and 0.01, respectively), while the rest LVEF was not ( P =0.18). The addition of LVEF reserve did not add any incremental value, while the addition of MBFR revealed incremental prognostic value (hazard ratio per 0.1 unit decrease in MBFR=1.08 [95% CI, 1.05–1.11], P <0.001) with fixed and reversible defects becoming nonsignificant ( P =0.07 and 0.29, respectively). There was no interaction between MBFR and cause of cardiomyopathy (ischemic versus nonischemic). Conclusions: In patients with a known cardiomyopathy who did not require early revascularization, reduced MBFR as obtained by positron emission tomography myocardial perfusion imaging is associated with all-cause mortality while other positron emission tomography myocardial perfusion imaging measures were not.